Molecular and Cellular Mechanisms of Rapid-Acting Antidepressants Ketamine and Scopolamine - S. Wohleb, Eric; Gerhard, Danielle; Thomas, Alex; S. Duman, Ronald (Current Neuropharmacology, 2017)
Major depressive disorder (MDD) is a prevalent neuropsychiatric disease that causes profound social and economic burdens. The impact of MDD is compounded by the limited therapeutic efficacy and delay of weeks to months of currently available medications. These issues highlight the need for more efficacious and faster-acting treatments to alleviate the burdens of MDD. Recent breakthroughs demonstrate that certain drugs, including ketamine and scopolamine, produce rapid and long-lasting antidepressant effects in MDD patients. Moreover, preclinical work has shown that the antidepressant actions of ketamine and scopolamine in rodent models are caused by an increase of extracellular glutamate, elevated BDNF, activation of the mammalian target of rapamycin complex 1 (mTORC1) cascade, and increased number and function of spine synapses in the prefrontal cortex (PFC). Here we review studies showing that both ketamine and scopolamine elicit rapid antidepressant effects through converging molecular and cellular mechanisms in the PFC. In addition, we discuss evidence that selective antagonists of NMDA and muscarinic acetylcholine (mACh) receptor subtypes (i.e., NR2B and M1-AChR) in the PFC produce comparable antidepressant responses. Furthermore, we discuss evidence that ketamine and scopolamine antagonize inhibitory interneurons in the PFC leading to disinhibition of pyramidal neurons and increased extracellular glutamate that promotes the rapid antidepressant responses to these agents. Collectively, these studies indicate that specific NMDA and mACh receptor subtypes on GABAergic interneurons are promising targets for novel rapid-acting antidepressant therapies.
Keywords: antidepressant